2004
DOI: 10.17660/actahortic.2004.634.17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Olive Germplasm in Iran on the Basis of Morphological Traits: Assessment of 'Zard' and 'Rowghani' Cultivars

Abstract: Iran, located in the Eastern Mediterranean, shares many geographical characteristics and common historical roots with the countries of the Mediterranean basin, which are home to the major known cultivars of olive. Iran, for its part, harbors numerous olive cultivars, whose morphological and biological characters are yet to be characterized. This is important both from commercial and nutritional points of view. Building upon earlier work and in conjunction with a molecular genetics program for molecular charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The data confirmed the suitability of multivariate analysis as a basis for further selection on a wider range of individuals. There was no grouping of 'Žutica' individuals according to the location, as was observed in studies of the varieties 'Zard' and 'Rowghani' [Hosseini-Mazinani et al 2004] and 'Oblica' [Strikic et al 2009].…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The data confirmed the suitability of multivariate analysis as a basis for further selection on a wider range of individuals. There was no grouping of 'Žutica' individuals according to the location, as was observed in studies of the varieties 'Zard' and 'Rowghani' [Hosseini-Mazinani et al 2004] and 'Oblica' [Strikic et al 2009].…”
Section: Resultsmentioning
confidence: 59%
“…Characterization of the material using multivariate analyses (PCA and cluster analysis) enabled us to gain an overall view of variability amongst the accessions based on the complete range of traits. PCA has been used in the evaluation of olive germplasm [Cantini et al 1999, Trentacoste andPuertas 2011] and in analysis of olive genetic diversity [Bandelj et al 2002, Hosseini-Mazinani et al 2004, Hannachi et al 2008, Uylaşer et al 2008, Strikic et al 2009, Zaher et al 2011. The PCA used in our work showed that more than 91% of observed variability was explained with the first three components, similar to the results reported by Cantini et al [1999] for olive accessions in the germplasm collection in Italy.…”
Section: Resultsmentioning
confidence: 99%
“…Reference cultivars were selected based on a previous characterization of Iranian olive cultivars [17], [25] and samples were derived from the Tarom and Rudbar collections. The 85 samples represent a wide range of olive trees from the Iranian plateau, directly collected from their original sites of spreading.…”
Section: Methodsmentioning
confidence: 99%
“…RAPD technique has been employed to develop genetic fingerprints and to assess genetic diversity in a wide range of mango (Ismail, 2003). Several reports came out in which RAPD genetic markers were used in order to identify Olive cultivars and to determine genetic relationships among them (Hosseini-Mazinani and Samaee, 2004).…”
Section: Rapd -Pcr Analysismentioning
confidence: 99%